Genetic determinants of plasma von Willebrand factor antigen levels: a target gene SNP and haplotype analysis of ARIC cohort - Campos, Marco; Sun, Wei; Yu, Fuli; Barbalic, Maja; Tang, Weihong; Chambless, Lloyd E; Wu, Kenneth K; Ballantyne, Christie; Folsom, Aaron R; Boerwinkle, Eric; Dong, Jing-Fei (Blood, 2011)
von Willebrand factor (VWF) is an essential component of hemostasis and has been implicated in thrombosis. Multimer size and the amount of circulating VWF are known to impact hemostatic function. We associated 78 VWF single nucleotide polymorphisms (SNPs) and haplotypes constructed from those SNPs with VWF antigen level in 7856 subjects of European descent. Among the nongenomic factors, age and body mass index contributed 4.8% and 1.6% of VWF variation, respectively. The SNP rs514659 (tags O blood type) contributed 15.4% of the variance. Among the VWF SNPs, we identified 18 SNPs that are associated with levels of VWF. The correlative SNPs are either intronic (89%) or silent exonic (11%). Although SNPs examined are distributed throughout the entire VWF gene without apparent cluster, all the positive SNPs are located in a 50-kb region. Exons in this region encode for VWF D2, D', and D3 domains that are known to regulate VWF multimerization and storage. Mutations in the D3 domain are also associated with von Willebrand disease. Fifteen of these 18 correlative SNPs are in 2 distinct haplotype blocks. In summary, we identified a cluster of intronic VWF SNPs that associate with plasma levels of VWF, individually or additively, in a large cohort of healthy subjects.